Vitamin D distribution by month, sex, and season in Turkey, Niğde province: A retrospective cohort study: D vitamin status in Niğde, Turkey - Bayram, Ergül; Ayan, Durmuş; Balcı, Tevfik; Zeybek Aydoğan, Kader; Inan, Dogan Bahadır; Karabay, Umut (Journal of Surgery and Medicine, 2024)
Background/Aim: Epidemiological investigations consistently indicate a widespread deficiency and insufficiency of vitamin D on a global scale. Vitamin D deficiency can lead to various acute and chronic diseases, including pre-eclampsia, autoimmune disorders, cardiovascular diseases, certain cancers, type 2 diabetes, and neurological disorders. However, the relationship between vitamin D status and its implications for global and public health has not been comprehensively explored. Notably, the differing clinical decision thresholds for diagnosing vitamin D deficiency and insufficiency established by various associations can create diagnostic confusion. Therefore, our study aimed to assess the distribution of vitamin D levels in Niğde province, considering variations by month, gender, and season, with respect to the clinical decision thresholds defined by different associations. Methods: The study sample comprised 57,731 cases (71% women and 19% men) admitted to our hospital between January 2021 and December 2022. We retrospectively evaluated 25-hydroxyvitamin D (25(OH)D) levels based on months, seasons, age, and gender. Additionally, we examined 25(OH)D levels separately using the clinical decision thresholds set by the Vitamin D Council, the Endocrine Society, and the Food and Nutrition Board. Patients with chronic renal insufficiency, hepatic insufficiency, and gastrointestinal malabsorption were excluded from the study, encompassing patients of all age groups. Furthermore, we categorized patients into different age decades and analyzed their vitamin D levels. We compared the same months in 2021 and 2022, monitoring changes in vitamin D levels throughout the year. Vitamin D levels were measured using the electrochemiluminescence assay (ECLIA) on a Roche Cobas E801 instrument. Results: When comparing the same months in 2021 and 2022, there was no statistically significant decrease or increase in 25(OH)D levels (The P-values for January and December were 0.066, 0.395, 0.907, 0.465, 0.705, 0.541, 0.625, 0.860, 0.695, 0.549, 0.892, and 0.838, respectively). Vitamin D insufficiency was observed in 70.3% of women and 29.7% of men. Participants under one year of age exhibited the highest mean 25(OH)D level (34.9 ng/mL), while participants between 20 and 29 years of age had the lowest mean 25(OH)D level (15.7 ng/mL). The lowest mean 25(OH)D level was recorded in April 2022 (15.6 ng/mL), whereas the highest mean 25(OH)D level was observed in July 2021 (22.7 ng/mL). There was a slight negative correlation between age and 25(OH)D levels (r=-0.038, P<0.001). The Vitamin D Council classification identified the highest number of patients with vitamin D deficiency (n=50,833; 88%). The Food and Nutrition Board included the lowest number of patients with vitamin D deficiency (n=15,049; 26.1%). Conclusion: Vitamin D deficiency is prevalent in Niğde province, particularly among women, and remains a significant public health concern. We advocate for the adoption of a unified clinical decision threshold and the expansion of the national vitamin D supplementation program to encompass adolescents and adults.